PENGARUH LATAR BELAKANG PENDIDIKAN, PENDIDKAN BERKELANJUTAN, ETIKA PROFESI, BUDAYA ORGANISASI DAN PEMAHAMAN GOOD GOVERNANCE TERHADAP HASIL KINERJA AUDITOR PEMERINTAH (Studi Kasus Pada Badan Pemeriksa Keuangan/ BPK-RI Perwakilan Provinsi Riau) - Maulina Agustiningsih; Nur Azlina '; Rusli ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aimed to know existence the influence of education background,continues educations, profesional ethics, organization culture, and knowledge good governance face share which government pereformance audit results at Audit Board Of the Republic Of Indonesia/ BPK-RI Delegation Riau Province. Population used is the of auditors working on the Audit Board Of the Republic Of Indonesia/ BPK-RI Delegation Riau Province housed in Pekanbaru totaling 55 people, with samples obtained many as 32 people, with a sampling census sampling technique.Tools used statistical test is the program Statistical Product and Service Solution (SPSS) ver. 17. Windows and Microsoft Excel 2007. The Researche result show taht: 1) the education background have a influence significant on the results of the performance of goverment auditors, 2) continuing education have a influence significant on the results of the performance of goverment auditors, 3) profesional ethichs have a influence significant on the results of the performance of goverment auditors, 4) organization culture have a influence significant on the results of the performance of goverment auditors, and 5) knowledge good governance have a influence significant on the results of the performance of goverment auditors.Keywords: The result of the performace of government auditors, educational background, countinuing education, profesional ethics, organizational culture, and knowledge of good governace.